2021
DOI: 10.18415/ijmmu.v8i9.2921
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Advertising and Price Discounts on the Interest of Tourists to Stay at Hotel (Staycation) During the Covid-19 Pandemic with Health Risk Perception as Moderating Variable

Abstract: This study aims to analyze and determine the significance of the effect of advertising and price discounts on interest in staying at hotels (staycation) during the Covid-19 pandemic, and to determine the role of health risk perception in moderating the relationship between advertising and price discounts on interest of tourist in staying at hotels in Lombok Island. The type of research used is causal research. The population in this study is the people of the island of Lombok aged between 20 to 60 years old an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Price Discount (H 4 ) was found to directly affect BI. This result is in accordance with literature that has demonstrated that price discounts have the potential to boost BI (Hu & Yang, 2019), as Price Discounts have a direct influence on consumer value perceptions (Yusnita et al, 2021). However, this finding does not support the literature showing that Price Discounts do not encourage BI (Zhi et al, 2023).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Price Discount (H 4 ) was found to directly affect BI. This result is in accordance with literature that has demonstrated that price discounts have the potential to boost BI (Hu & Yang, 2019), as Price Discounts have a direct influence on consumer value perceptions (Yusnita et al, 2021). However, this finding does not support the literature showing that Price Discounts do not encourage BI (Zhi et al, 2023).…”
Section: Discussionsupporting
confidence: 76%
“…COVID-19 era research has generally shown that this feature, along with others (e.g., advertising) (Yusnita et al, 2021), positively affects BI. However, this has been explored with other features (e.g., offer timing, customer type, consumer reviews, and bundling of mixed membership promotions Wen et al, 2021;Zhi et al, 2023).…”
Section: Price Discount Promotionmentioning
confidence: 96%
“…COVID-19 has created significant perceptions of health risks among individuals at tourism destinations. The likelihood of contracting COVID-19 and its associated expenditures are the biggest concerns for travelers during the pandemic [52]; therefore, insurance, free mask distribution, and free quarantine in the case of COVID-19 infection can be effective strategies with which to revive the tourism industry in the new normal. A price discount is a very common way to induce people to buy something, giving them something extra that makes them want to make a purchase immediately [53].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…A price discount is a very common way to induce people to buy something, giving them something extra that makes them want to make a purchase immediately [53]. Yusnita et al [52] described the fact that discounts have a significant relationship with buying behaviors. Similarly, Alkatiri et al [54] stated that advertising policies have positive effects on the buying attitudes of individuals.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Along with this phenomenon, many hotels provide very competitive prices to attract visitors. Public interest in doing staycations is predicted to increase during the Covid-19 pandemic, even some hotels offer staycation packages with prices and offers that are quite attractive [6,7].…”
Section: Introductionmentioning
confidence: 99%